Abdominal versus thoracic approach for myotomy in esophageal achalasia. - de Almeida, J C (1992)
Miotomy is the most common operation for the treatment of achalasia of the esophagus. The most important complication of this operation is gastro-esophageal reflux, and controversy exists in the choice of a thoracic or abdominal approach to this operation. From 1974 until 1988, our group performed 45 miotomies for achalasia of the esophagus. Follow-up was obtained in 82% of the patients. The thoracic approach was used in 21 cases (tor), and 24 patients were operated through an abdominal approach (abd). All the miotomies had an anti-reflux procedure associated. Post-operative evaluation consisted of: clinical score determination; endoscopy with biopsy; manometry; 24 Phmetry. The clinical score revealed that 47% of the patients in the group tor were asymptomatic, and in the group abd this rate was 53%. Absence of macroscopic esophagitis was registered in 75% of the patients in the group tor, and in 91% in the group abd. Microscopic esophagitis was observed in 42% of the cases in the group tor, and in 45% of the group abd. Manometry revealed a low pressure in the inferior esophageal sphincter in 90% of the cases of the group tor, and in 80% of the group abd. Pathological gastro-esophageal reflux, detected by 24 h Phmetry, was present in 29% of the group tor, and in 36% of the group abd. The results in these two groups were very similar, uniformly favourable, and without evidence of superiority of either operation. The choice of a thoracic, or abdominal approach should depend on associated factors such as patient age, respiratory disease, etc.